Las Posadas recreates story of Christmas (Raton, NM Raton Range, 1993)
Article about Las Posadas reenactment on First Street. It is a traditional enactment of the biblical story of Joseph and Mary as they return to their hometown of Bethlehem (Belen) for the census.
Newspaper article
Master list item #: 34
File location is in the Raton file Cabinet
Keywords: Palomino, Mike -- Raton Musuem Curator; Raton Musuem; New Mexico Arts Division; New Mexico Community Foundation; Arts and Humanities Council; Christmas Celebration; Christmas Performance; Religious Customs; Biblical Story; Spanish Customs; Missionary priests; Southwest New Mexico; Raton, New Mexico; Historic First Street